1994
DOI: 10.1091/mbc.5.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Inositol polyphosphates are not increased by overexpression of Ins(1,4,5)P3 3-kinase but show cell-cycle dependent changes in growth factor-stimulated fibroblasts.

Abstract: NIH 3T3 fibroblasts were stably transfected with rat brain inositol 1,4,5-trisphosphate (Ins(1,4,5)P3) 3-kinase to explore the relationship between increased production of Ins(1,3,4,5)P4 and the formation of InsP5 and InsP6. Mass measurements of InsP5 and InsP6 revealed no significant difference between kinase- and vector-transfected fibroblasts. However, such 3-kinase-transfected cells, when labeled with [3H]inositol for 48-72 h, showed lower levels of [3H]InsP5 and [3H]InsP6, as well as [3H]Ins(1,3,4,6)P4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Three molecular studies indicate that IP 3 3-kinases are not involved in IP 5 and IP 6 synthesis. 1) Balla et al (45) suggested that overexpression of IP 3 3-kinase did not increase higher inositol polyphosphates such as IP 5 and IP 6 in NIH 3T3 cells; 2) IP 3 3-kinase mouse knock-out cells reveal that IP 5 and IP 6 production is unaltered (46 -48); and 3) in Drosophila melanogaster loss of IP 3 3-kinase isoforms does not decrease IP 6 levels, but loss of dmIpk2 nearly ablates IP 5 and IP 6 (41).…”
Section: Discussionmentioning
confidence: 99%
“…Three molecular studies indicate that IP 3 3-kinases are not involved in IP 5 and IP 6 synthesis. 1) Balla et al (45) suggested that overexpression of IP 3 3-kinase did not increase higher inositol polyphosphates such as IP 5 and IP 6 in NIH 3T3 cells; 2) IP 3 3-kinase mouse knock-out cells reveal that IP 5 and IP 6 production is unaltered (46 -48); and 3) in Drosophila melanogaster loss of IP 3 3-kinase isoforms does not decrease IP 6 levels, but loss of dmIpk2 nearly ablates IP 5 and IP 6 (41).…”
Section: Discussionmentioning
confidence: 99%
“…This information, together with the new data on the kinetic parameters for Ins(1,3,4,5,6)P 5 and InsP 6 phosphorylation by mammalian type 1 InsP 6 kinase (Table II), indicates that both of these substrates will compete for phosphorylation by this enzyme in vivo. If the size of the metabolic reservoir of either substrate is modified, as happens for example during passage through the cell cycle (30,31), the metabolism of all of the diphosphorylated compounds will be affected. From this intertwined metabolism, we can further conclude that the physiological activities of all of the diphosphorylated inositol phosphates are likely to be closely linked.…”
Section: Discussionmentioning
confidence: 99%
“…Inositol phosphates were then resolved on two complementary high performance liquid chromatography (HPLC) systems [8,9] …”
Section: Yeast Culturing and Radiolabeling With [ 3 H]inositolmentioning
confidence: 99%